IMPLEMENTASI LITERASI TERHADAP APLIKASI EASILY APPLICABLE GRAPHICAL LAYOUT EDITOR BERBASIS PENDIDIKAN ISLAM - Arief Goeritno; Dian Anwar; Syaiful Syaiful; Ritzkal Ritzkal; Ahya Ibadina Syahida; Rezi Setria (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2018)
On Islamic education for students of SMK Elektronika, it has been done summary material about application with image brands (brand image) Easily Applicable Graphical Layout Editor (EAGLE) by literacy approach. EAGLE application is one of the principals of fundamental Islamic education in the material form. The literacy of EAGLE application material, including general explanation and important notes to the EAGLE application. A common explanation of the EAGLE application which is one of the many applications for the draft in the manufacture of pieces of printed boards (printed cicuit board, PCB) computer-assisted (computer aided design, CAD), so as layout editor is easy to use to help draft board printed circuit (PCB). EAGLE application consists of three main modules, namely the Layout Editor, Schematic Editor, and Autoroutes embedded in a single user interface. All three can be accessed from EAGLE's User Interface (UI) or user interface on EAGLE application, so there is no need to change netlists between the scheme and layout. Some advantages of the EAGLE application, namely (i) cross-program (cross platform), where EAGLE can operate on the operating system (Operating System), either Windows, Mac, or Linux, (ii) the need for storage is small, there are editions free use (free of charge) or can also have the low cost, and (iii) support of the community. Important notes for implementation literacy to EAGLE application, grouped in five vital records, namely (a) view basis, (b) creation with project new and schematic, (c) reinforcement board layout, (d) loading pathways among parts (routes of parts), and (e) checking rules for design (design rule check, drc).